Recognition and Assessment of Digital Scholarly Outputs in the Humanities - Maryl, Maciej (Septentrio Conference Series, 2023)
Watch VIDEO. In recent years we have observed an increase in digital practices and outputs in scholarship, which should be understood as a standard evolution of scholarly practices to take advantage of digital technologies. And although written genres, such as the monograph or essay, remain dominant in the humanities, the range of technological possibilities allow scholars to redefine those forms of expression and enrich them with other media or genres. However, as the opening example showed, this innovation is not supported by the assessment system, or even sometimes takes place in spite of it. A change in attitude requires recognition of three key aspects of digital humanities work: (1) its interdisciplinarity in borrowing tools and methods from ICT or social sciences; (2) the new research practices which should be recognised as valid scholarly work; (3) innovative scholarly outputs that go beyond the traditional genres but provide valid research results. This presentation discusses the recommendations of the ALLEA E-Humanities Working Group with regards to the assessment of novel scholarly communication genres in the humanities. The work is based on the group’s previous report, Sustainable and FAIR Data Sharing in the Humanities, which provided recommendations on data practices in the humanities. The current focus is on attuning institutional policies to emerging scholarly needs in connection to current research assessment reform (CoARA). The recommendations are prepared in close cooperation with stakeholders and the research community. It underwent an open consultation whereby we collected more than 200 comments from the public. The final draft is under preparation and will be published in fall 2023. The ALLEA E-Humanities Working Group recommendations are meant to serve as guidance for institutions and evaluators to embrace innovative outputs in the humanities and thus create space for their development. The Working Group has prepared tailored recommendations which could be divided into two main groups. First, the group focuses on the cross-cutting issues pertinent to digital practices in the humanities, which are (1) linking studies with underlying data, (2) updating and versioning of the outputs, (3) collaboration and authorship, (4) training and competence building, and (5) reviewing. Next, we discuss particular case studies of innovative outputs where cross-cutting issues manifest themselves, such as digital scholarly editions, extended publications, databases, visualisations, code and blogs. The overall conclusions provide some general remarks on recognising and evaluating digital practices in the humanities.